Proposing a regional gender equality index (R-GEI) with an application to Italy. Issue 5 (4th May 2021) - di Bella, Enrico; Leporatti, Lucia; Gandullia, Luca; Maggino, Filomena
ABSTRACT: Gender equality represents a central topic of our society, and its study is gaining increasing attention in the international panorama. During the last 20 years, various indicators aiming at measuring gender equality have been proposed, but there are no systematic experiences of indicators tailored for a subnational analysis. We propose a regionalization of the most complete and detailed gender equality indicator, the gender equality index (GEI) of the European Institute on Gender Equality, choosing Italy as a case study. The results show how a regionalized approach to gender equality is necessary to set priorities and target regional policy actions.